RATIO DECIDENDI PENETAPAN PENGESAHAN (ITSBAT) NIKAH DI PENGADILAN AGAMA - Muhammad Khusnul Yakin (Universitas Airlangga, 2015)
Phenomena that occur in society marriage only refers to the Islamic religious law met the requirements and harmonious marriaege, so it can be said only based on article 2, paragraph (1) of Constitution Number 1 of 1974 on Mariage, lawful religion also means lawful state, but their marriage is not based on article 2, paragraph (2) provisions on orders registration of marriage, known as a marriage under the hand. Marriage Constitution set is limited to marriages performed before the law was enacted, but the religious court based on legal considerans accept and grant approval under the hand of marriage to marriage after the Marriage Constitution enacted by basing on the Compilation of Islamic Law article 7, paragraph 3.